PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT DAN IMPLIKASINYA TERHADAP PENGHINDARAN PAJAK - Pardomuan Ritonga (Universitas Multimedia Nusantara, 2022)
Abstract- This research is aim to analyze the influence of corporate social responsibility and audit committee on audit quality and implications with tax avoidance. This type of research is quantitative. The research population is sub-sectors of finance company listed in the Indonesia Stock Exchange in 2016-2020. Data processing in this research using Statistical Program for Social Science 22 program. The sampling method using purposive sampling technique is counted 16 companies. The method of analysis using linear regression analysis and sobel test. These results indicate that corporate social responsibility and audit committee both have significant effect simultaneously on the audit quality as long as corporate social responsibility and audit committee both have negative significant effect simultaneously on the tax avoidance. The partial test results showed that both of corporate social responsibility and audit committee had to the audit quality. However, corporate social responsibility and audit committee have no indirect effect to the tax avoidance through audit quality. Keywords: Corporate Social Responsibility; Audit Committee; Audit Quality; Tax Avoidance.